Can training promote employee organizational commitment? The effect of employability and expectation value. Issue 2 (27th May 2014) - Ling, Ling; Qing, Tao; Shen, Peng
Abstract : Purpose: – This paper aims to provide theoretical analysis and empirical study on the relationship between training and organizational commitment; analyze the mediating role of employability and the moderating role of expectation value in their relationship; and draw from both of these to suggest practical implications to organizations aiming to effectively train and retain employees, and for employees themselves. Design/methodology/approach: – First, the paper reviews the literature regarding training, employability, organizational commitment and expectation value. Second, it develops a theoretical model linking training, employability, organizational commitment and expectation value, and proposes a series of research hypotheses. Third, drawing on samples of 405 Chinese employees, it tests hypotheses based on a series of measurement and statistical analyses. Last, it discusses the analysis results and puts forward related suggestions for management practice. Findings: – The paper tests and verifies the applicability of Western training and employability scales in China from a self-perception perspective. Training is positively related to organizational commitment and employability. Further, employability partly mediates the relationship between training and organizational commitment, and expectation value moderates the relationship between employability and organizational commitment. Research limitations/implications: – First, the cross-sectional design prevents the making of causal statements. Future research should adopt an experimental (quasi experimental) research method or longitudinal research to study the casual relationship between variables. Second, data are from employees' self-report, giving rise to concern about possible common source bias. Future research should allow supervisors to rate employees' employability or provide evaluation of employees' expectation value to collect multi-source data. Originality/value: – The paper first introduces Western scales of training and employability into a Chinese context, and then tests and verifies the two scales' applicability in China. To explain the action mechanism of training to the employee – organizational commitment in a boundaryless career, the paper constructs a moderate mediation model to test the direct effect of training on organizational commitment, the mediating effect of employability and the moderating effect of expectation value. This study complements past research by investigating both the mediating and moderating mechanisms in training organizational commitment.